ANALISIS MANAJEMEN PEMBINAAN BERBASIS PENDIDIKAN KARAKTER KRISTEN BAGI ANAK DIDIK PEMASYARAKATAN (ANDIKPAS) PADA LEMBAGA PEMBINAAN KHUSUS ANAK KELAS II AMBON - Imelda Ch Pocerattu (IAKN Ambon, 2022)
The Convention on the Rights of the Child, which is part of Human Rights, affirms and forms children's rights which categorically consist of 4 types, namely the rights to survival, the rights to protection, the rights to development (development rights), and the right to participate (participation rights). It is explained in more detail, especially in the third point regarding the child's right to development (development rights), that the right to grow and develop is a child's rights which include all forms of formal and non-formal education and the right to achieve a decent standard of living for development. spiritual, mental, physical, moral and social of children. Correctional Students (Andikpas) often feel they are the scum of society and have a bleak future. Therefore, there is a need for Andikpas coaching, especially character building at the Special Children's Correctional Institution (LPKA) so that Andikpas becomes a good and responsible member of society. To achieve this goal, coaching management needs to be done well, so that the results of coaching have a long-term effect and can have a positive impact on all andikpas. The management that is carried out must be in accordance with the Christian faith, so that the character that is formed is a reflection of the Christian attitude of life.